High Prescribing and State-Level Variation in Z-Drug Use Among Medicare Patients - Anderson, Kaitlin E.; Gifeisman, Rachel I.; Basting, James L.; Harris, Donovan J.; Rajan, Antonica R.; McCall, Kenneth L.; Piper, Brian J. (Pharmacopsychiatry, 2023)
Background Z-drugs are nonbenzodiazepine hypnotics used for sleep initiation and maintenance; these drugs increase the risk of fall-related injuries in older adults. The American Geriatrics Society’s Beers criteria classifies Z-drugs as high-risk and strongly recommends avoiding prescribing Z-drugs to older adults due to adverse effects. The study objectives were to determine the prevalence of Z-drug prescribing among Medicare Part D patients and identify state or specialty-dependent prescribing differences. This study also aimed to determine prescribing patterns of Z-drugs to Medicare patients.Methods Z-drug prescription data was extracted from the Centers for Medicare and Medicaid Services State Drug Utilization Data for 2018. For all 50 states, the number of prescriptions per 100 Medicare enrollees and days-supply per prescription was determined. The percentage of total prescriptions prescribed by each specialty and the average number of prescriptions per provider within each specialty was also determined.Results Zolpidem was the most prescribed Z-drug (95.0%). Prescriptions per 100 enrollees were significantly high in Utah (28.2) and Arkansas (26.7) and significantly low in Hawaii (9.3) relative to the national average (17.5). Family medicine (32.1%), internal medicine (31.4%), and psychiatry (11.7%) made up the largest percentages of total prescriptions. The number of prescriptions per provider was significantly high among psychiatrists.Discussion Contrary to the Beers criteria, Z-drugs are prescribed to older adults at high rates.
Keywords: elderly; older adult; zolpidem; zopiclone; zaleplon